A LINGUSTIC STUDY OF VOCATIVE FORMS IN THE NOVEL "EMMA" BY JANE AUSTIN - ENAS NAJI KADIM, ASST. PROF. (مجلة كلية التربية, 2021)
This paper investigates the style of vocative forms in English language by using a novel" Emma" by Jane Austin as data. First this paper will indicate the definitions and the main lexical forms of the term vocative .Then this paper will discuss the linguistic levels of this phenomena which are the semantic , sociolinguistic , and pragmatic levels .This paper also clarifies the functions of vocative and the implications of vocatives in relation to politeness strategies in society .In addition to that this paper will indicate the main models of vocative phenomena in English language .Finally the researcher applies the statistical analysis of the vocative structures which are uttered by the characters of the novel .